ANALYSIS OF THE EFFECT OF COMPENSATION, ORGANIZATIONAL CULTURE AND MOTIVATION ON NON ASN EMPLOYEE PERFORMANCE - Karman, Abd.; Pasryb, Andi Syahida Ulhaq (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
Human resources are fundamental capital to fulfill company goals. There is a need for reliable human resources to achieve goals and compete with other companies, therefore HR management is needed to organize, manage, and utilize employees. Employee performance is one indicator of good resources so it can be used as material for evaluating employee work to maintain or improve company performance. This study aimed to determine the variables that influence employee performance at IAIN Fattahul Muluk Papua, namely compensation, organizational culture, and motivation. Sampling in the study was a saturated sample of 46 people. The data analysis method in this study is the classic assumption test and multiple linear regression with processing using SPSS. The results showed that compensation and motivation did not affect performance, but work culture influenced performance. When all variables were tested together, a significant effect was found on the performance of non-ASN employees of IAIN Fattahul Muluk Papua.